Komunikasi Spiritual dalam Ritual Pemakaman Korea pada Film Exhuma (2024) - Tirta, Evaria; Paramita, Sinta (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This study explores the representation of spiritual communication in Korean funeral rituals as depicted in the film Exhuma (2024). Using Charles Sanders Peirce's semiotic approach, the researcher identifies how visual, auditory, and gestural signs form patterns of communication between humans and spirits rooted in Korean cultural traditions. The theoretical framework used includes the concepts of spiritual communication, Peirce's semiotics, and the study of ritual symbols related to the use of incense, offerings, trance, ritual songs, and symbolic objects. This study uses descriptive qualitative methods through audiovisual observation and literature review. The results show that the film establishes spiritual communication through three stages: invocation through mantras and ritual objects, interaction through trance in the medium, and purification through symbolic offerings. The entire process is shaped by the relationship between icons, indices, and symbols that construct spiritual meaning in the film's narrative. The study concludes that Exhuma represents Korean spiritual traditions through a sign structure that reflects ancestral reverence and ritual communication patterns, thus functioning as a medium for conveying cultural and spiritual values. Penelitian ini menggali representasi komunikasi spiritual dalam ritual pemakaman Korea yang ditampilkan dalam film Exhuma (2024). Dengan menggunakan pendekatan semiotika Charles Sanders Peirce, peneliti mengidentifikasi bagaimana tanda visual, auditori, dan gestural membentuk pola komunikasi manusia dan roh yang berakar pada tradisi budaya Korea. Kerangka teori yang digunakan mencakup konsep komunikasi spiritual, semiotika Peirce, serta kajian simbol ritual yang berkaitan dengan penggunaan dupa, sesaji, trance, nyanyian ritual, dan objek simbolik. Penelitian ini menggunakan metode kualitatif deskriptif melalui observasi audiovisual dan kajian pustaka. Hasil penelitian menunjukkan bahwa film membangun komunikasi spiritual melalui tiga tahapan, yaitu pemanggilan melalui mantra dan benda ritual, interaksi melalui trance pada medium, serta penyucian melalui persembahan simbolik. Seluruh proses tersebut dibentuk oleh hubungan ikon, indeks, dan simbol yang menyusun makna spiritual di dalam narasi film. Penelitian menyimpulkan bahwa Exhuma merepresentasikan tradisi spiritual Korea melalui struktur tanda yang mencerminkan penghormatan leluhur dan pola komunikasi ritual, sehingga film berfungsi sebagai media penyampai nilai budaya dan spiritual.